The role of color interior design systems and their relationship to visual reception For scenes of theatrical performances (Journal of the College of Basic Education, 2022)
This research deals with (the role of chromatic interior design systems and their relationship to visual reception of theatrical scenes), As the role that color plays within the visual scenography’s reception of the scenes of theatrical performances is a research problem represented in the predominant shortcomings of theatrical performances in a number of design aspects in general and with regard to the visual reception of color systems in particular, As these color systems are important in the integration of the public space of the scenes of theatrical performance, as well as the importance posed by the subject of visual reception and its relationship to the color interior design system.Therefore, the research aimed to reveal the role of the color system employed in the interior design of the scenes of theatrical performances and its relationship to the visual recipient. The research also determined the theatrical performances of Kirkuk governorate, in which the play (Sarab) was chosen as a model for descriptive analysis.The research came out with a set of results, including: The employment of the appropriate color system in terms of color values and its connotations through visual discourse played an active role in achieving the functional goal and the aesthetic diversity of theatrical performance.The research also came out with a set of conclusions, including: that there is a precise correlation between the technical and psychological foundations that characterize colors, According to this harmony and the outcomes of its color relationship from aesthetic and psychological influences.